Milk production, milk composition and body weight change of crossbred dairy cows in urban and peri-urban dairy production systems in Ethiopia - Mekasha, Yoseph; Tegegne, Azage; Yami, A.; Umunna, N.N. (Ethiopian Society of Animal Production, 2003)
Milk yield, milk composition and body weight change of crossbred dairy cows (Holstein Friesian X Zebu) were studied in the urban and peri-urban dairy production systems in the Addis Ababa milk shed between December 1997 and November 1998. Ninety-seven cows, with parities above two and at the beginning of lactation, representing three production sub-systems (intra-urban, large peri-urban and secondary town) were considered for the study. Daily milk production, milk yield in a 305-day lactation and fat corrected milk production varied (P<0.001) among sub production systems. Dairy cows in secondary town farms had 13.4, 26.3 and 20.2% greater mean daily, 305- day and lactation milk yield compared with intra and peri-urban farms respectively. Concentrations of milk fat and total solids differed (P<0.001) among the production sub-systems. Lactation yield (P<0.05), lactation length (P<0.01) and concentrations of milk fat (P<0.01), protein and total solids (P<0.001) differed among herd sizes groups. Body weight varied (P<0.001) among production sub-systems, with cows in secondary town farms being heavier and cows in intra-urban farms lighter. It is therefore concluded that the various environmental factors, mainly nutrition, and genetic factors, possibly inbreeding depression, should be improved in order to improve milk production from intensively managed urban and peri-urban dairy farms